Ultrahigh-strength structural steel with excellent welding joint performance and production method of ultrahigh-strength structural steel

By optimizing chemical composition and heat treatment process, and using the precipitation strengthening effect of VC nanoprecipitates, the problem of low strength and toughness of welded joints of ultra-high strength structural steel is solved, and the performance of high-strength and high-toughness is achieved.

CN119800213APending Publication Date: 2025-04-11BAOSHAN IRON & STEEL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311312651.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing 1000MPa grade ultra-high strength structural steel often has low strength and toughness of welded joints after welding. Although the high Mo content increases the strength of the welding heat-affected zone, it will deteriorate toughness and increase cold crack sensitivity.

Method used

By optimizing chemical composition, using a low Mo or no Mo design, adding higher V elements to form a large number of VC nanoprecipitates, giving full play to the precipitation strengthening effect of VC, replacing Mo elements to improve the strength of the steel plate, and controlling the content and size of VC nanoprecipitates to ensure the high strength and high toughness of the welded joints.

Benefits of technology

It realizes high strength and high toughness of steel plates and welded joints, reduces welding crack sensitivity, avoids the negative impact of high Mo content on toughness, and meets users' requirements for high strength and high toughness of welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800213A_ABST
    Figure CN119800213A_ABST
Patent Text Reader

Abstract

The invention discloses ultrahigh-strength structural steel with excellent welding joint performance and a production method thereof. The ultrahigh-strength structural steel comprises the following chemical components in percentage by weight: 0.15-0.21% of C, less than or equal to 0.50% of Si, 0.60-1.60% of Mn, 0-0.030% of Ti, 0.061-0.15% of V, 0-0.060% of Nb, 0-0.003% of RE, 0.65-1.20% of Cr, 0-0.25% of Mo, 0-0.30% of W, 0-0.30% of Ni, 0-0.40% of Cu, 0.0005-0.0030% of B, 0.02-0.06% of Al, 0.0005-0.004% of Ca, less than or equal to 0.005% of N, less than or equal to 0.020% of P, less than or equal to 0.0050% of S and the balance of Fe In addition, the relational expression that 1021 * V + 523 * W + 416 * Mo + 81.3 * Cr is larger than or equal to 220 and smaller than or equal to 430 needs to be met at the same time. By means of the heat treatment process, the size of VC precipitates is refined, the strengthening effect of the VC precipitates is fully exerted, the steel plate and a welding joint have high strength and toughness, the requirements of a user for high strength and high toughness of steel plate welding are met, and the low welding crack sensitivity is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of structural steel, and in particular to ultra-high-strength structural steel with excellent welding joint performance and a production method thereof. Background Art

[0002] Hot-rolled ultra-high-strength steel for engineering machinery with a yield strength of 1000MPa is mainly used to manufacture components such as crane booms and pump truck feeder booms, which places high demands on the strength, plasticity, low-temperature toughness and fatigue properties of the steel plates. Traditional 1000MPa ultra-high-strength steel is generally produced by offline tempering heat treatment or online quenching + tempering process to obtain tempered martensitic structure. After the ultra-high-strength steel is welded with carbon dioxide gas shielded welding, the strength and toughness of the welded joints are often low. This is due to the decomposition and recrystallization of martensite in the high-temperature heat-affected zone during welding. Some steel companies resist tempering softening by adding higher Mo elements, but too much Mo addition can easily lead to embrittlement of the weld heat-affected zone.

[0003] Chinese patent CN103014538B discloses "a high-strength steel plate with a yield strength of 960 MPa and a method for manufacturing the same", the weight percentage of which is: C: 0.08-0.12%, Si: 0.36-1.00%, Mn: 1.2-1.6%, P≤0.015%, S≤0.010%, Al: 0.02-0.04%, Ti: 0.01-0.03%, N≤0.006%, Ca≤0.005%, and one or more of Cr≤0.70%, Ni≤0.30%, and Mo≤0.30%, and the balance is iron and unavoidable impurities. The invention adopts appropriate carbon content, appropriate cheap alloy elements Si and Mn, adds less precious alloy elements Cr, Ni and Mo, does not add Cu, Nb, V, B and other elements, combines heating, controlled rolling, rapid cooling after rolling and online rapid tempering, and the steel plate structure presents tempered martensite (may also contain a small amount of residual austenite) and carbide. The steel plate has a yield strength of ≥960MPa, an elongation A50 ≥18%, and an Akv of -60°C ≥50J. However, the welding performance of the steel plate is not mentioned.

[0004] Chinese patent CN102134680A discloses "an ultra-high strength steel with a yield strength of 960 MPa and its production method". The chemical composition of the steel is as follows by weight: C: 0.07-0.09%, Si: 0.15-0.25%, Mn: 1.00-1.20%, Cr: 1.05-1.15%, Mo: 0.15-0.20%, Al: 0.01-0.06%, P≤0.02%, S≤0.01%, N≤0.008%, and the rest is Fe and unavoidable impurities. The lower carbon and manganese content, the addition of more Cr elements and a small amount of Mo elements to improve the hardenability and control the structure after quenching and tempering treatment, without adding precious alloy elements such as Nb, Ni, Cu, etc., the yield strength of the material after heat treatment can reach more than 960 MPa, and it has good plasticity and toughness. There is no mention of the welding performance of the steel plate.

[0005] Chinese patent CN112553526A discloses "a 960MPa grade ultra-high strength structural steel, steel pipe and its working method and application", the main components of which are C: 0.12-0.17%, Mn: 0.7-1.3%, Cr: 0.5-1.0%, Mo: 0.70-1.0%, W: 0.1-0.3%, etc. The invention adds higher Mo, and the impact energy at -40℃ is only 45J.

[0006] Chinese patent CN111455269A discloses "Marine steel plate with yield strength of 960 MPa or even higher and its manufacturing method". The main chemical composition is C: 0.07-0.15%, Si: 0.02-0.15%, Mn: 0.80-1.3%, Mo: 0.40-0.70%, Ni: 1.0-2.0%, V: 0.03-0.06%, Cu: 0.20-0.50%, etc. This patent adds higher Mo, Ni and Cu elements.

[0007] Chinese patent CN102560274A discloses "a kind of quenched and tempered ultra-high strength steel with a yield strength of 1000 MPa and its preparation method". The chemical composition of the steel plate is (by weight), C: 0.15-0.20%, Si: 0.10-0.40%, Mn: 1.00-1.50%, Cr: 0.30-0.50%, Mo: 0.30-0.50%, Ni: 0.20-0.50%, B: 0.0010- 0.0030%, Nb: 0.010~0.030%, V: 0.030~0.050%, Ti: 0.010~0.020%, Alt: 0.030~0.050%, P≤0.020%, S≤0.010%, the rest is Fe and unavoidable impurities, carbon equivalent Ceq(%)=C+Mn / 6+(Cr+Mo+V) / 5+(Cu+Ni) / 15:0.50~0.60. Through offline heat treatment, tempered troostite structure is obtained after tempering, upper yield strength ReH≥1000MPa, tensile strength Rm≥1040MPa, elongation after fracture A=10~18%, -40℃ impact value AKv=30~90J. Gas shielded welding is used for welding, and the hardness of the heat affected zone reaches about 300 Vickers hardness, and the heat-affected low-temperature toughness is not tested.

[0008] Chinese patent CN102505096A discloses "an ultra-high strength engineering machinery steel with excellent performance and its manufacturing method", which adopts the composition system of medium C-medium Mn-(Ti+Nb+B) microalloyed steel as the basis, appropriately increases the acid-soluble Als content in the steel, optimizes the DQ+offline tempering process (T), that is, uses the ausforming process (rapid cooling from the deformed austenite, inheriting the deformation strengthening effect (i.e. deformation dislocation) to the final microstructure, while promoting the nucleation of martensite laths on the deformation substructure and the deformation steps of the original austenite grain boundary and competitive growth along different orientations, resulting in the newly formed martensite laths being small, effectively dividing the original austenite grains, resulting in small and uniform packets and large orientation differences between blocks), so that the microstructure of the finished steel plate is fine low-carbon tempered martensite, the average cluster size is below 20μm, and an ultra-high strength steel plate with excellent low-temperature toughness is obtained.

[0009] Existing 1000MPa-level ultra-high strength structural steel usually adds a higher Mo content, generally only considering the mechanical properties of the steel plate, not the welding processing performance of the steel plate, or only considering the hardness of the welded joint. Engineering machinery requires a lot of welding. Although a higher Mo content can improve the strength of the heat-affected zone of welding, it will deteriorate the toughness and increase the sensitivity of cold cracks. Strict preheating before welding and post-weld heat treatment are usually required. Outdoor operations in winter often do not have the conditions for preheating before welding and post-weld heat treatment, which is prone to welding cracking problems. Summary of the invention

[0010] The purpose of the present invention is to provide an ultra-high strength structural steel with excellent welding joint performance and a production method thereof, so as to ensure that the steel plate has high strength and good welding joint processability, the yield strength of the steel is ≥1000MPa, the tensile strength is ≥1050MPa, and the elongation A 50 >20%, -60℃ impact energy>90J; after conventional carbon dioxide gas shielded welding, the tensile strength of the welded joint is ≥980MPa, and the -40℃ impact energy of the heat affected zone is>60J, which meets the user's requirements for high strength and high toughness of welding and has low sensitivity to welding cracks.

[0011] In order to achieve the above object, the technical solution provided by the present invention is:

[0012] An ultra-high strength structural steel with excellent welding joint performance, the chemical composition weight percentage of which is C: 0.15-0.21%, Si≤0.50%, Mn: 0.60-1.60%, Ti: 0-0.030%, V: 0.061-0.15%, Nb: 0-0.060%, RE: 0-0.003%, Cr: 0.65-1.20%, Mo: 0-0.25%, W: 0-0.30%, Ni: 0-0.30%, Cu: 0-0.40%, B: 0.0005-0.0030%, Al: 0.02-0.06%, Ca: 0.0005-0.004%, N≤0.005%, P≤0.020%, S≤0.0050%, and the rest includes Fe and other inevitable impurities; and the above elements need to satisfy the following relationship at the same time:

[0013] 220≤1021×V+523×W+416×Mo+81.3×Cr≤430.

[0014] Furthermore, the remainder is Fe and other inevitable impurities.

[0015] The microstructure of the ultra-high strength structural steel of the present invention is tempered troostite and a large amount of VC nano-precipitates, wherein the content of the VC nano-precipitates is 0.07-0.18wt%, and the size of the VC nano-precipitates is 2-5nm.

[0016] The yield strength of the ultra-high strength structural steel of the present invention is ≥1000MPa, the tensile strength is ≥1050MPa, and the elongation A 50 >20%, -60℃ impact energy>90J; the tensile strength of the welded joint after conventional carbon dioxide gas shielded welding is ≥980MPa, and the -40℃ impact energy of the heat affected zone is>60J.

[0017] In the composition design of the present invention:

[0018] Carbon: solid solution strengthening, adjusting the strength and plasticity of martensite structure. According to the test, the tensile strength of low carbon martensite after reheating and quenching is related to the C content as follows: Rm = 2510C (%) + 790 (MPa). After quenching, tempering is used to further adjust the strength, plasticity and toughness. A high C content will lead to an increase in the overall C equivalent, which is easy to cause cracks during welding. Therefore, the present invention controls the C content to 0.15-0.21%.

[0019] Silicon: A certain amount of Si can play a good deoxidation role, and at the same time inhibit the precipitation of carbides during tempering and improve the toughness of steel. Too high Si content is prone to produce red iron scale. Therefore, the present invention controls the silicon content to ≤ 0.50%.

[0020] Manganese: Mn element above 0.8% can improve the hardenability of steel, while Mn content exceeding 1.6% is prone to segregation and inclusions such as MnS, which deteriorates the toughness of martensitic high-strength steel. Therefore, the present invention controls the Mn content to 0.60-1.60%.

[0021] Titanium: Ti is a microalloying element. When rolling and coiling, it can form nano-scale precipitates with elements such as C and N. It strongly inhibits the growth of austenite grains during heat treatment. During welding, a trace amount of Ti (C, N) precipitates can inhibit the growth of austenite and play a role in improving the toughness of the welding heat-affected zone. Therefore, the titanium content is controlled at 0 to 0.030% in the present invention.

[0022] Vanadium: V is a key microalloying element of the present invention. VC will precipitate during rolling and coiling. During heat treatment, the steel plate is heated to a high temperature of (Tvc+80) to 1050°C and kept warm for 15 to 30 minutes to completely dissolve VC. Then, it is tempered and kept warm for 20 to 90 minutes at 480 to 580°C to precipitate nano-level VC, which has a precipitation strengthening effect. Therefore, the present invention controls the vanadium content to 0.061 to 0.15%.

[0023] Niobium: Nb is a microalloying element, which forms nano-scale precipitates with C element, inhibits the growth of austenite grains during hot rolling, and further refines the structure after phase transformation. Therefore, the present invention controls the niobium content to be 0-0.060%.

[0024] Rare earth: A trace amount of RE will form a composite compound with TiN during steelmaking, modify the shape of cubic TiN, control the growth of harmful TiN, and improve the toughness and plasticity of steel. During welding, it will combine with the dispersed VC precipitates to inhibit the growth of VC precipitates and give full play to the precipitation strengthening effect of micro-nano VC precipitates in the heat affected zone of welding. Therefore, the present invention controls the RE content to 0-0.003%.

[0025] Chromium: Cr can improve the hardenability of steel and is conducive to the formation of full martensite structure during quenching. At the same time, it has a certain effect of resisting the softening of the welding heat affected zone during welding, and works together with Mo, W and VC to ensure that the strength of the welding heat affected zone reaches more than 980MPa. Therefore, the present invention controls the Cr content to 0.65-1.20%.

[0026] Molybdenum: A certain amount of Mo element can improve the hardenability of steel, which is conducive to the formation of full martensite structure during quenching. Mo inhibits the diffusion of C element during welding and has a certain effect of resisting softening of welding heat affected zone. Too high Mo content will lead to an increase in carbon equivalent and reduce the toughness of welding heat affected zone. Therefore, the present invention controls the Mo content to 0-0.25%.

[0027] Tungsten: The effect of W is similar to that of Mo, and it has a strong effect of resisting softening of the heat affected zone of welding. Too much W will reduce the toughness of the heat affected zone of welding. Therefore, the present invention controls the W content to be 0-0.30%.

[0028] Nickel: A certain amount of Ni element has the effect of refining the martensitic structure and improving the toughness of steel. Too high a Ni content will increase the carbon equivalent and deteriorate the welding performance. Therefore, the present invention controls the Ni content to be 0-0.30%.

[0029] Copper: The Cu element can produce a certain precipitation strengthening effect during tempering. In addition, adding a certain amount of Cu element can improve the corrosion resistance of ultra-high strength steel for engineering machinery. Therefore, the present invention controls the Cu content to be 0-0.40%.

[0030] Boron: A small amount of B can improve the hardenability and strength of steel. B exceeding 0.0030% is prone to segregation and forms carbon-boron compounds, which seriously deteriorates the toughness of steel. Therefore, the present invention controls the boron content to 0.0005-0.0030%.

[0031] Aluminum: Al above 0.02% can be used as a deoxidizer, and a small amount of Al2O3 can refine the grains when the slab is heated, thereby refining the microstructure of the steel plate after rolling. However, when the Al content exceeds 0.06%, Al oxide inclusion defects are easily generated. Therefore, the present invention controls the Al content to 0.02-0.06%.

[0032] Calcium: trace amounts of Ca can purify molten steel during steel smelting, optimize the shape and size of inclusions such as MnS, and improve the toughness of steel; Ca content exceeding 0.004% is likely to form larger Ca compounds, which will deteriorate toughness. Therefore, the present invention controls the Ca content to 0.0005-0.004%.

[0033] Nitrogen: Since the present invention adds more V, V easily reacts with N to form a certain amount of VN during hot rolling, which consumes a certain amount of V and reduces the precipitation strengthening effect of VC. Therefore, the present invention strictly controls the N content to be below 0.0050%.

[0034] Phosphorus and sulfur: P and S, as impurity elements, affect the plasticity and toughness of steel. Therefore, the present invention strictly controls them, P≤0.020%, S≤0.0050%.

[0035] The present invention defines the welding joint strength control index WI after research, WI = 1021 × V + 523 × W + 416 × Mo + 81.3 × Cr, which comprehensively reflects the strength contribution of VC micro-nano precipitates in the welding heat affected zone and the effect of W, Mo, and Cr elements on resisting high temperature tempering softening by inhibiting carbide diffusion and martensite decomposition. The present invention forms a large number of VC nano precipitates in the organization by adding a relatively high V content, wherein the VC nano precipitate content is 0.07-0.18%, and the size of the VC nano precipitates is 2-5 nm, giving full play to the precipitation strengthening effect of VC on the welding heat affected zone, effectively resisting the softening of the heat affected zone during welding, therefore, V has the highest contribution coefficient to the strength of the welding joint; W and Mo form carbon compounds by inhibiting C diffusion during welding, which also contributes to the strength of the welding heat affected zone to a certain extent; Cr also produces carbon compounds during welding, which has a certain effect of improving the strength of the welding heat affected zone. If the WI is added excessively and is lower than 220, the strength of the weld joint cannot reach 980MPa, and if the WI is higher than 430, the toughness of the weld heat affected zone will be deteriorated. The present invention uses VC precipitation strengthening to replace the Mo element to obtain a higher strength of the steel plate, avoid the influence on the toughness, ensure the strength of the steel plate and the weld joint, and obtain better toughness.

[0036] The method for producing ultra-high strength structural steel with excellent welding joint performance of the present invention comprises the following steps:

[0037] 1) Smelting and casting

[0038] Smelting and casting according to the above chemical composition to form a casting billet;

[0039] 2) Heating

[0040] The heating temperature of the ingot is 1230-1300℃. When the core of the ingot reaches the heating temperature, the insulation begins. The insulation time is >2.0h.

[0041] 3) Rolling and coiling

[0042] The controlled rolling and controlled cooling process is adopted, with the coiling temperature at 550-650℃ and air cooling to room temperature after coiling;

[0043] 4) Heat treatment

[0044] Quenching treatment: the steel plate is heated to (Tvc+80)~1050℃, kept at this temperature for 15~30min, and then rapidly cooled to room temperature at a cooling rate of ≥150℃ / s; wherein Tvc is the melting temperature of VC, Tvc=7041 / (4.7-lg(V×C), unit is ℃; V and C are the weight percentages of the corresponding elements in the chemical composition of ultra-high strength steel respectively;

[0045] For tempering treatment, the steel plate is reheated to 480-580°C, kept warm for 20-90 minutes, and then air-cooled to room temperature.

[0046] In the method for producing ultra-high strength structural steel with excellent weld joint performance of the present invention:

[0047] In the billet heating process, the slab is heated to 1230-1300°C, and the insulation is started after the core of the billet reaches the heating temperature. The insulation time is greater than 2 hours to allow the alloy elements to diffuse evenly.

[0048] The coiling temperature of the present invention is 550-650°C, and the coiling is air-cooled to room temperature. It usually takes more than 3 days for the conventional hot-rolled steel coil to cool to room temperature after coiling, and the VC will be coarsened. The present invention subsequently adopts a heat treatment process to refine the VC.

[0049] In the heat treatment process, the steel plate is heated to a high temperature of (Tvc+80)~1050℃ and kept warm for 15~30min to completely dissolve the coarsened VC. Tvc is the minimum solid solution temperature of VC, Tvc=7041 / (4.7-lg(V×C), unit ℃, where V and C are the weight percentages of the corresponding elements in the chemical composition of ultra-high strength steel. Due to the short heating time, a higher superheat is required to fully dissolve the coarsened VC in the rolled steel plate. However, too high a heating temperature and too long a holding time will lead to coarsening of austenite grains, especially when the heating temperature exceeds 1050℃, the austenite grains will grow abnormally, and the coarse austenite will lead to coarsening of the troostite structure after quenching and tempering, thereby deteriorating the toughness of the steel plate. Therefore, the heating of the steel plate is controlled at (Tvc+80)~1050℃.

[0050] After that, rapid cooling is adopted, and the steel plate is rapidly cooled to room temperature at a cooling rate of ≥150℃ / s to obtain a martensite structure; after quenching, the steel plate is tempered, and the tempered martensite structure can be obtained by tempering the steel plate at 480-580℃. At the same time, 480-580℃ is the best precipitation temperature for nano-scale VC. The temperature is kept for more than 20 minutes to make the solid solution VC re-precipitate, and 0.07-0.18% of VC nano-precipitates are produced. The size of VC nano-precipitates is controlled at 2-5nm. When the temperature is kept for more than 90 minutes, the VC nano-precipitates are easy to coarsen. The generated VC nano-precipitates can produce a precipitation strengthening contribution of more than 150MPa, give full play to the precipitation strengthening effect of VC nano-precipitates, and effectively prevent the softening of the welding heat affected zone.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] The present invention adopts a low-Mo or Mo-free design in terms of component design. By adding a relatively high V element, VC precipitation strengthening is fully utilized to replace the Mo element so that the steel plate obtains a relatively high strength, and a large number of VC nano-precipitates are formed in the organization, wherein the content of the VC nano-precipitates is 0.07-0.18%, and the precipitation strengthening effect of the VC nano-precipitates is fully utilized, and 220≤1021×V+523×W+416×Mo+81.3×Cr≤430 is controlled, so that the steel plate and the welded joint have relatively high strength, and also have good low-temperature toughness of the welded joint, and reduce the sensitivity of welding cracks; and the influence of excessively high Mo element addition on the toughness of the steel plate is avoided.

[0053] On the basis of the composition design, the present invention increases the heating temperature of the steel plate in the heat treatment process, heats the steel plate temperature to (Tvc+80)~1050℃, and shortens the holding time to 15~30min to ensure that VC is completely dissolved. After quenching, the tempering temperature is controlled at 480~580℃ and kept at 20~90min to make the dissolved VC precipitate again in nano form, effectively ensuring the contribution of VC precipitation strengthening and effectively preventing the softening of the welding heat affected zone. The traditional heat treatment heating temperature is usually 860~900℃, the purpose is to austenitize the ferrite and pearlite structures in the steel plate, and the precipitation of VC in the rolled steel plate is not considered. Therefore, the VC in the traditional heat treatment may not have time to be dissolved or only a small amount of solid solution, and the precipitation strengthening effect of VC on the welding heat affected zone is not effectively exerted.

[0054] The present invention gives full play to the precipitation strengthening effect of VC on the welding heat affected zone through composition and process design, ensuring that both the steel plate and the welded joint can obtain high strength and high toughness. The yield strength of the steel plate after heat treatment is ≥1000MPa, the tensile strength is ≥1050MPa, the elongation A50>20%, and the impact energy at -60℃>90J; the tensile strength of the welded joint after conventional carbon dioxide gas shielded welding is ≥980MPa, and the impact energy at -40℃ of the heat affected zone is >60J, which has low welding crack sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a typical optical microscope metallographic structure diagram of the steel plate of Example 5 of the present invention.

[0056] Figure 2 This is a typical scanning electron microscope metallographic structure diagram of the steel plate of Example 5 of the present invention.

[0057] Figure 3 Schematic diagram of a welded joint when steel plates are welded in an embodiment of the present invention. DETAILED DESCRIPTION

[0058] The present invention will be further described below in conjunction with the embodiments.

[0059] The production process of the ultra-high strength structural steel of the present invention is: smelting (converter or electric furnace), casting→heating→rolling→coiling→heat treatment.

[0060] The specific components and process parameters of the embodiments of the present invention are shown in Table 1 and Table 2, and the properties of the steel plates of each embodiment are shown in Table 3.

[0061] Figure 1 and Figure 2 The optical microscope metallographic structure photos and scanning electron microscope metallographic structure photos of the steel in Example 5 are given respectively. Figure 1 It can be seen that the metallographic structure of the finished steel plate is uniform equiaxed tempered martensite. Figure 2 It can be seen that VC precipitates are in the form of particles, and the size of VC precipitates is between 2 and 5 nm.

[0062] Welding performance test:

[0063] The steel plate obtained by the present invention is subjected to carbon dioxide gas shielded welding, the groove is a single-sided 60° V-shaped, argon-rich gas shielded welding is adopted, the shielding gas is 80% Ar+20% CO2, the welding material is BH1000-II gas shielded welding wire with a diameter of Φ1.2mm, and welding is performed for 3 passes. The specific welding process is shown in Table 4, and the joint schematic diagram is shown in Figure 3 shown.

[0064] After welding, the joint tensile test is carried out in accordance with the standard GB / T 2651-2008 "Welded joint tensile test method". For specific welded joint test performance, see Table 5.

[0065] The present invention designs the chemical composition and the heat treatment process so that the performance of the steel plate and the welded joint after the heat treatment reaches ultra-high strength and high toughness.

[0066]

[0067]

[0068]

[0069]

[0070]

Claims

1. An ultra-high strength structural steel with excellent welding joint performance, the chemical composition weight percentage of which is C: 0.15-0.21%, Si≤0.50%, Mn: 0.60-1.60%, Ti: 0-0.030%, V: 0.061-0.15%, Nb: 0-0.060%, RE: 0-0.003%, Cr: 0.65-1.20%, Mo: 0-0.25%, W: 0-0.30%, Ni: 0-0.30%, Cu: 0-0.40%, B: 0.0005-0.0030%, Al: 0.02-0.06%, Ca: 0.0005-0.004%, N≤0.005%, P≤0.020%, S≤0.0050%, and the rest includes Fe and other inevitable impurities; and the above elements need to satisfy the following relationship at the same time: 220≤1021×V+523×W+416×Mo+81.3×Cr≤430.

2. The ultra-high strength structural steel with excellent welding joint performance as claimed in claim 1, characterized in that: The rest is Fe and other inevitable impurities.

3. The ultra-high strength structural steel with excellent weld joint performance as claimed in claim 1 or 2, characterized in that: The microstructure of the ultra-high strength structural steel is tempered troostite and a large amount of VC nano-precipitates, wherein the content of the VC nano-precipitates is 0.07-0.18wt%, and the size of the VC nano-precipitates is 2-5nm.

4. The ultra-high strength structural steel with excellent weld joint performance as claimed in claim 1, 2 or 3, characterized in that: The yield strength of the ultra-high strength structural steel is ≥1000MPa, the tensile strength is ≥1050MPa, and the elongation is A 50 >20%, -60℃ impact energy>90J; after conventional carbon dioxide gas shielded welding, the tensile strength of the welded joint is ≥980MPa, and the -40℃ impact energy of the heat affected zone is>60J.

5. The method for producing ultra-high strength structural steel with excellent weld joint performance as claimed in any one of claims 1 to 4, characterized in that: The steps include: 1) Smelting and casting Smelting and casting according to the chemical composition of claim 1 or 2 to form a casting billet; 2) Heating The heating temperature of the ingot is 1230-1300℃. When the core of the ingot reaches the heating temperature, the insulation begins. The insulation time is >2.0h. 3) Rolling and coiling The controlled rolling and controlled cooling process is adopted, with the coiling temperature at 550-650℃ and air cooling to room temperature after coiling; 4) Heat treatment Quenching treatment, heating the steel plate to (Tvc+80)~1050℃, keeping the temperature for 15~30min, and then rapidly cooling to room temperature at a cooling rate of ≥150℃ / s; wherein Tvc is the melting temperature of VC, Tvc=7041 / (4.7-lg(V×C)), unit is ℃; V and C are the weight percentages of the corresponding elements in the chemical composition of ultra-high strength structural steel respectively; For tempering treatment, the steel plate is reheated to 480-580°C, kept warm for 20-90 minutes, and then air-cooled to room temperature.

6. The production method according to claim 5, characterized in that The obtained ultra-high strength structural steel has a microstructure of tempered troostite and a large amount of VC nano-precipitates; wherein the content of the VC nano-precipitates is 0.07-0.18wt%, and the size of the VC nano-precipitates is 2-5nm.

7. The production method according to claim 5 or 6, characterized in that: The yield strength of the obtained ultra-high strength structural steel is ≥1000MPa, the tensile strength is ≥1050MPa, and the elongation is A 50 >20%, -60℃ impact energy>90J; after conventional carbon dioxide gas shielded welding, the tensile strength of the welded joint is ≥980MPa, and the -40℃ impact energy of the heat affected zone is>60J.

Citation Information

Patent Citations

  • Ultrahigh strength steel with 960MPa of yield strength and production method thereof

    CN102134680A

  • A high-strength steel plate with a yield strength of 960 MPa and its manufacturing method

    CN103014538B

  • Ultrahigh-strength maritime steel plate with yield strength of 960MPa and manufacturing method thereof

    CN111455269A

  • 960MPa-grade ultrahigh-strength structural steel, steel pipe and manufacturing method and application of 960MPa-grade ultrahigh-strength structural steel

    CN112553526A

  • Steel with good property and ultra-high strength for engineering machinery and manufacturing method thereof

    CN102505096A